Handzeichnungen - Graphik : Neuerwerbungen 1965/66 - Kataloge der Graphischen Sammlung Kestner-Museum Hannover VIII. (Hannover : Kestner-Museum, 1967)
Isenstein, Harald ; Masson, André ; Schlemmer, Oskar ; Schwitters, Kurt ; Braque, Georges ; Buchholz, Wolff ; Cestnik, Franz ; Dali, Salvador ; Eliasberg, Paul ; Heckel, Erich ; Hinsch, Wendelin ; Kliemann, Carl Heinz ; Munch, Edvard ; Pechstein, Max ; Picasso, Pablo ; etc.
boek